USE OF MONOLITHIC REINFORCED CONCRETE STRUCTURES IN THE TERRITORY OF THE REPUBLIC OF UZBEKISTAN - Akhmedov Islombek; S.Kholmirzayev; Umarov Isroil; F.Dadaxanov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. This article presents the results of experimental studies and relevant conclusions on the influence of various factors on the structural safety of monolithic reinforced concrete structures, as well as the study of the properties of various strong concrete.